Pollen limitation and xenia effects in a cultivated mass-flowering tree, Macadamia integrifolia (Proteaceae). (2nd September 2021) - Trueman, Stephen J; Kämper, Wiebke; Nichols, Joel; Ogbourne, Steven M; Hawkes, David; Peters, Trent; Hosseini Bai, Shahla; Wallace, Helen M
Abstract: Background and Aims: Pollen limitation is most prevalent among bee-pollinated plants, self-incompatible plants and tropical plants. However, we have very little understanding of the extent to which pollen limitation affects fruit set in mass-flowering trees despite tree crops accounting for at least 600 million tons of the 9200 million tons of annual global food production. Methods: We determined the extent of pollen limitation in a bee-pollinated, partially self-incompatible, subtropical tree by hand cross-pollinating the majority of flowers on mass-flowering macadamia ( Macadamia integrifolia ) trees that produce about 200 000–400 000 flowers. We measured tree yield and kernel quality and estimated final fruit set. We genotyped individual kernels by MassARRAY to determine levels of outcrossing in orchards and assess paternity effects on nut quality. Key Results: Macadamia trees were pollen-limited. Supplementary cross-pollination increased nut-in-shell yield, kernel yield and fruit set by as much as 97, 109 and 92 %, respectively. The extent of pollen limitation depended upon the proximity of experimental trees to trees of another cultivar because macadamia trees were highly outcrossing. Between 84 and 100 % of fruit arose from cross-pollination, even at 200 m (25 rows) from orchard blocks of another cultivar. Large variations in nut-in-shell mass, kernel mass, kernel recovery and kernel oil concentration were related to differences in fruit paternity, including between self-pollinated and cross-pollinated fruit, thus demonstrating pollen-parent effects on fruit quality (i.e. xenia). Conclusions: This study is the first to demonstrate pollen limitation in a mass-flowering tree. Improved pollination led to increased kernel yield of 0.31–0.59 tons ha –1, which equates currently to higher farm-gate income of approximately US3720–US7080 ha –1 . The heavy reliance of macadamia flowers on cross-pollination and the strong xenia effects on kernel mass demonstrate the high value that pollination services can provide to food production.